IN SILICO STUDY OF NEW ACETAZOLAMIDE ANALOGUES BEARING THIAZOLE MOIETY WITH PROMISING CARBONIC ANHYDRASE INHIBITORY ACTIVITY - ABDULHUSSEIN, HUSSEIN I.; NASER, NOOR H. (International Journal of Applied Pharmaceutics, 2026)
Objective: Cancer is the second leading cause of death worldwide. Multiple targets can be hit for cancer treatment; carbonic anhydrase enzyme XII is one of these targets because it plays a vital role in the tumour microenvironment. Methods: ADMETlab 3.0 platform used to predict (absorption, distribution, metabolism, excretion, and toxicity) characteristics, while molecular docking managed by the molecular operating environment program MOE 2015.1. Results: The molecular docking analysis revealed that all nineteen designed compounds exhibited favourable binding affinities toward carbonic anhydrase enzymes XII (PDB ID: 1JD0) and IX (PDB ID: 3IAI), and most of the designed compounds satisfy the predominant drug-likeness requirements. Conclusion: Acetazolamide's binding affinity for the carbonic anhydrase enzyme can be enhanced by including a substituted thiazole ring.